Paciente masculino de 32 años con diagnóstico de neumonía viral - Villalva Álvarez, Anthony Juver (2021)
The pathology called pneumonia is an infection of the pulmonary parenchyma, which presents high morbidity and mortality, mainly distinguished by respiratory manifestations, fever and radiological findings. They are most frequently caused by bacteria and viruses, both are difficult to differentiate clinically, their clinical and causal behavior varies according to the age group and the probable location where this infection was acquired (community-acquired or hospital-acquired pneumonia). The term atypical or viral pneumonia describes the unusual manifestation of pneumonias. The term has evolved to be much broader in meaning, described as pneumonia caused by a group of viruses (respiratory syncytial virus (RSV), influenza virus, parainfluenza virus, adenovirus (less common), coronavirus such as SARS-CoV-2 which is the cause of covid pneumonia).